Islamic Business Ethics Implementation In Marketing Communication of Hajj/Umrah Travel Agency “X” Surabaya - Prasetyo, Ari; Pratiwi, Intan Kusuma (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2016)
This research aims to explorethe implementation of Islamic business ethics in marketing communications Umrah/Hajj travel agency “X” Tour and Travel. This research uses qualitative descriptiveapproach with explanatory case studies as a type of qualitative research Islamicbusiness ethics which becomes reference in this study SIFAT (Shiddiq, Istiqamah,Fathanah, Amanah and Talbligh). The technique used is the data collectionthrough interviews with President and Marketing Manager “X” Tour and Travel,and participatory observation for two weeks at the operational office of “X” Tourand Travel. To support the data obtained from the results of the interviews as wellas participatory observation, research is also equipped with the results of interviewswith jamaah who have used the services of “X” Tour and Travel. The research resultsindicate that “X” Tour and Travel has implemented Shiddiq, Istiqamah, Fathanah,Amanah, and Tabligh in marketing communications.DOI: 10.15408/aiq.v8i1.2510